2022
DOI: 10.21608/adjalexu.2021.92675.1214
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Efficacy of Botulinum Toxin a for Improving Facial Scars (Randomized Clinical Trial)

Abstract: INTRODUCTION:Scars widen when the underlying musculature (frontalis muscles, procerus, and corrugator supercilii muscles) pulls apart suture lines, and scars oriented against relaxed skin tension lines (RSTL) are especially susceptible to these distraction forces. Because botulinum toxin A (BTA) induces complete muscle paralysis, the purpose of the current study was to evaluate the effects of BTA using both observer dependent qualitative assessments and quantitative measurements to verify its beneficial effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…Our attempt at early injection of botulinum toxin was consistent with a number of studies, as suggested by Sheta et al (9) who suggested that injection of botulinum toxin in the first 5 days after wound closure could improve forehead scar appearance. Additionally, Kim et al (23) reported successful results for thyroidectomy scars after 6 days of injection of botulinum toxin type A.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our attempt at early injection of botulinum toxin was consistent with a number of studies, as suggested by Sheta et al (9) who suggested that injection of botulinum toxin in the first 5 days after wound closure could improve forehead scar appearance. Additionally, Kim et al (23) reported successful results for thyroidectomy scars after 6 days of injection of botulinum toxin type A.…”
Section: Discussionsupporting
confidence: 82%
“…Wide hypertrophic scars have been an issue, but various solutions have been proposed; however, none of them prevent the pathologic process that causes wide hypertrophic scars, which is the distracting force of muscular pull. Since BTA toxin, which is generated by Clostridium botulinum, is a powerful neurotoxin that causes muscle paralysis by blocking acetylcholine release at the neuromuscular junction, it can be applied to reduce all tensile stresses coming from a surgical wound's underlying muscles (8,9).…”
Section: Introductionmentioning
confidence: 99%